Description and biological notes of the first species of Xenos (Strepsiptera: Stylopidae) parasitic in Polistes carnifex F. (Hymenoptera: Vespidae) in Mexico - Kathirithamby, Jeyaraney; Hughes, David P. (Zootaxa, 2006)
A description and biological notes on the first species of Xenos (X. hamiltoni) (Strepsiptera: Stylopidae) parasitic in Polistes carnifex F. from Mexico is given. A list of Strepsiptera and their hosts from Mexico is provided.